VISCOELASTIC LITHOSPHERE DEFORMATION MODEL ON STRIKE-SLIP FAULTS: STRAIN ACCUMULATION AND STRAIN RELEASE - Ain Bening, Maulidia
Earthquakes are natural disasters that occur relatively frequently and are capable of causing significant losses. Therefore, the estimation of earthquakes occurrence is a constant need. Modeling is one of the methods used to predict the occurrence of earthquakes. Earthquakes can occur when deformation happens in the lithosphere in a strike-slip fault. The lithosphere is the outermost layer of the Earth's crust, consisting of an elastic-brittle upper crust and an elastic-viscous lower crust and upper mantle. A viscoelastic lithosphere deformation in the strikeslip fault can be modeled using the finite-element method. In this case, the lithosphere deformation model in strike-slip fault is observed from strain accumulation and release. Each process represents the interseismic and coseismic phases of the earthquake cycle. In particular, the strain accumulation process is modeled by applying the frictional strength parameter. This model also varied the thickness of the two layers, namely the upper crust and lower crust along with the upper mantle, using three scenarios. The first scenario is used as a reference scenario; the second scenario applies a thinner upper crust than the reference scenario; and the third scenario applies a thicker upper crust than the reference scenario. Referring to the slip, displacement, and differential stress, this study shows that the use of elastic material in the upper crust and Maxwell's viscoelastic material in the lower crust and upper mantle can represent the behavior of the two layers observed. This behavior is shown from the differential stress on the elastic layer larger than the viscoelastic layer. This study also indicates that using a thicker viscoelastic layer ratio than the elastic layer can produce relatively small deformations. The large friction coefficient and cohesion will result in relatively small deformations. The friction coefficient gives a bigger on the lithosphere deformation model.